Relação entre a gestão de processos e a aprendizagem organizacional: estudo de caso em uma cooperativa de crédito central atuante no Nordeste - Cavalcanti, Karen de Lucena (2019)
Organizations continuously seek to improve their results through operational efficiency and one of the great challenges is to be able to develop organizational learning with this focus. One of the methods used to achieve operational efficiency is process management, however, there is little practical experience focusing on the relationship between process management and organizational learning. In this sense, the general objective of this study is to analyze the relationship between process management and organizational learning, focusing on the Registration Test process carried out by the Internal Control Unit of a Central Credit Cooperative operating in the Northeast region. To achieve the research objectives, qualitative methods were used with case study techniques, semi structured interview application and documentary analysis. The first stage consists of presenting the context of the institution where the study was carried out, integrated with Financial Cooperativism, and the theoretical context of process management and organizational learning, based on well-known authors in their fields of expertise such as Michael Hammer, Choo, Peter Senge, Enio Meiner and many others. Next, the process management was approached at the Central Credit Union, focusing on the mapping and redesign of the Cadastre Test flow, using BPMN methodology, Bizagi Modeler software and case study techniques. Still using the case study, this study also presented the phase of implementation of the standardized process and redesigned in the operational routine and training of the work team with the objective of analyzing if the process management can be used as complementary tool of organizational learning in the context of the organization where the study was conducted. Finally, using the information obtained from the interviews, the results of the study were presented, which converged with the theories presented and allowed to conclude that there is a positive relationship between process management and organizational learning, focusing on improving operational efficiency.